Exploring the parameter for alternating current electrophoretic deposition of carbon nanotubes-polypyrrole : a review / Annestasia Ollat Jampang, Intan Syaffinazzilla Zaine and Dr. Noirain Isa - Jampang, Annestasia Ollat; Zaine, Intan Syaffinazzilla; Isa, Norain (2020)
Carbon nanotubes (CNTs) is one of the most widely used carbonaceous materials aside from graphene and activated carbon. Electrophoretic deposition (EPD) of CNTs, especially in combination with polypyrrole (PPy), is receiving increasing attention from medical field and also electric and electronic field. This review has discussed key published work on factors related to the operation of AC-EPD and factors related to suspension of CNTs-PPy film formation. It has been shown that AC-EPD techniques can be used to obtain smooth and low bubble formation of film deposited on substrate electrode at high voltages from aqueous suspensions. This research paper was completed by the systematic review from previous journals method. The review was limited to studies published in 20 years back to see the evolution of EPD technique. For the factors related to operation, the wave frequency should be at the range of 0.01 Hz to 1 kHz by using sinusoidal wave. The deposition period is 4 minutes to 110 minutes depends on the wave frequency, waveform and the peak to peak voltage. Duty cycle for rectangular wave is 80%. The optimum range of peak to peak voltage is 16 V to 100 V. For factors related to suspension, the suggested medium of suspension is acetone and dispersing agent for CNTS-PPy composites is malachite green.